2022
DOI: 10.1039/d1ra08219a
|View full text |Cite
|
Sign up to set email alerts
|

A highly selective and sensitive “on–off” fluorescent probe for detecting cadmium ions and l-cysteine based on nitrogen and boron co-doped carbon quantum dots

Abstract: Schematic presentation of the synthesis of N,B-CQDs and their application as an “on–off” fluorescent probe for Cd2+ and l-Cys detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Figure 3(b,c) shows that in the wavelength range from 250 to 470 nm, the N‐CDs exhibited excitation wavelength dependence, which could be attributed to different emissive traps on the N‐CD surface. [ 32 ] The colour coordinates of the maximum excitation and emission wavelengths were (0.15, 0.12) (Figure 3d). Furthermore, the QY of the N‐CDs was 3.84%.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(b,c) shows that in the wavelength range from 250 to 470 nm, the N‐CDs exhibited excitation wavelength dependence, which could be attributed to different emissive traps on the N‐CD surface. [ 32 ] The colour coordinates of the maximum excitation and emission wavelengths were (0.15, 0.12) (Figure 3d). Furthermore, the QY of the N‐CDs was 3.84%.…”
Section: Resultsmentioning
confidence: 99%
“…Yan et al [149] reported a rapid and sensitive "turn-on" fluorescence sensor for detecting Cd 2+ based on N, B-doped CQDs, which may be ascribed to the formation of an N, B-CQDs/Cd 2+ complex, resulting in reduced internal charge transfer (ICT) and improved photo-generated electron transfer. Based on a similar co-doping system introduced for detection of Cr 6+ by Luo's group [150].…”
Section: Other Metal Ionsmentioning
confidence: 99%
“…1,2 Reportedly, abnormal levels of L-cysteine can assist in diagnosing various diseases such as hypogenesis, skin lesions, hepatic injury, decreased hematopoiesis, AIDS, Alzheimer's disease, Parkinson's, etc. [3][4][5][6] Moreover, L-cysteine plays an important role in medicine and the food industry, like being used as a food additive 7,8 and detoxifying heavy metals and radioactive drugs. 9 Considering the aforementioned properties, the detection of Lcysteine is of great signicance for human health and food quality assurance.…”
Section: Introductionmentioning
confidence: 99%